2018
DOI: 10.1016/j.eap.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Environmental management systems: Does certification pay?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
1
11
0
2
Order By: Relevance
“…Although some scholars doubt the effect of EM [33,34], our empirical research gives evidence that EM contributes to firms’ GPI. The implementation of EM could decompose the organization’s environmental objectives into middle-level departments and grass-root employees.…”
Section: Empirical Results and Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although some scholars doubt the effect of EM [33,34], our empirical research gives evidence that EM contributes to firms’ GPI. The implementation of EM could decompose the organization’s environmental objectives into middle-level departments and grass-root employees.…”
Section: Empirical Results and Discussionmentioning
confidence: 68%
“…Many scholars and business practitioners still have doubts about the effect of EM. They hold that it is not the core function of firms, but a decoration or even a burden [33,34]. Through the study of the influential mechanism, the research offers a conceptual framework that could remedy this theoretical deficiency and enhance the confidence of business in EM.…”
Section: Introductionmentioning
confidence: 99%
“…Even though certification related to international management system standards is voluntary, few companies, if any, are willing to forego certification, mostly due to the signaling effects. The study carried out by Frondel and coauthors [36] indicated that the application of management system standards without certification does not influence company performance at the same level as in the case of certified companies.…”
Section: Introductionmentioning
confidence: 99%
“…The first internal approach is characterized by the proactive and voluntary actions of the company. These actions are framed by the following:The proactive and voluntary implementation of an environmental management system that presents an ideal framework for the integration of the measurement tools, the environmental indicators and the auditing process (Zilahy, 2017; Frondel et al , 2018) or through the allocation of the environmental objectives (Saadi et al , 2011; Saadi and Djebabra, 2015);The deployment of knowledge management to yield the environmental knowledge that presents the necessary base for the proactive and voluntary actions (Djebabra et al , 2011). …”
Section: Introductionmentioning
confidence: 99%